Isolated hydatid cyst of adrenal gland with hypertension mimicking Conn’s syndrome: a very rare case - Chaudhary, Tarun; Agrawal, Shikhar; Biswas, Manoj; Sarpal, Rajeev; Shirazi, Nadia (International Journal of Research in Medical Sciences, 2017)
Hydatid cyst of the adrenal gland is one of the rare conditions caused by the larval stage of Echinococcus granulosus. The incidence of adrenal gland involvement is less than 1% of all hydatid disease in humans and isolated adrenal involvement is extremely rare. Hydatid disease is frequent in endemic regions and sheep farming areas with equal sex distribution. Here, a case of 23 year old female with isolated adrenal gland hydatid cyst is presented, that was evaluated clinically, investigated radiographicaly and by blood investigations and finally histopathology confirmed the diagnosis. No complications occurred at peri and postoperative period. The patient was given 6 cycles of albendazole (10 mg/kg in two divided doses), each for a period of four weeks followed by a week’s rest. The patient is on regular follow-up without recurrence in last 1 year.